Respuesta :

--------------------------------------------------------------------------
Equation
-------------------------------------------------------------------------- 
 [tex]y - 9 = - \dfrac{1}{2} (x + 2)[/tex]

--------------------------------------------------------------------------  
Rearrange the equation
-------------------------------------------------------------------------- 
[tex]y - 9 = - \dfrac{1}{2} (x + 2) \\ \\
y - 9 = - \dfrac{1}{2}x - 1 \\ \\
y - 9 + 9 = - \dfrac{1}{2}x - 1 + 9 \ \Longleftarrow \text{add 9 to both side} \\ \\
y = -\dfrac{1}{2}x + 8 [/tex]

--------------------------------------------------------------------------  
slope of the perpendicular line
-------------------------------------------------------------------------- 
slope = 2

(*the slope of the perpendicular line is the negative reciprocal of the slope of line)

---------------------------------------------------------------------------  
Substitute slope into equation y = mx + c
--------------------------------------------------------------------------- 
y = 2x + c

---------------------------------------------------------------------------  
Find y-intercept
--------------------------------------------------------------------------- 
y = 2x + c
At point (0, 4)
4 = 2(0) + c
c = 4

----------------------------------------------------------------------------  
Substitute y-intercept into the equation y = 2x + c
-----------------------------------------------------------------------------  
y = 2x + 4

----------------------------------------------------------------------------  
Answer: y = 2x + 4
----------------------------------------------------------------------------- 

ACCESS MORE